Women's Recovery from Sternotomy-Extension (WREST-E) study: examining long-term pain and discomfort following sternotomy and their predictors. Issue 4 (16th July 2007) - King, K M; Parry, M; Southern, D; Faris, P; Tsuyuki, R T
Abstract : Objective: To examine incision and breast pain and discomfort, and their predictors in women 12 months following sternotomy. Design: Extension survey following participation in a clinical trial. Setting: 10 Canadian centres. Patients: Women (n = 326) who completed the Women's Recovery from Sternotomy Trial. Interventions: None. Main outcome measures: Pain and discomfort data (numeric rating scales) collected by standardised interview at 5 days, 12 weeks and 12 months following sternotomy. Results: More patients reported having incision or breast discomfort (46.6%) than pain (18.1%) at 12 months postoperatively. No symptoms at 5 days postoperatively were significantly associated with symptom presence at 12 postoperative months. However, having incision pain and discomfort as well as breast pain and discomfort at 12 postoperative weeks was associated with incision pain (odds ratio (OR) = 3.26, 95% confidence interval (CI) 1.51 to 7.07), incision discomfort (OR = 4.87, 95% CI 3.01 to 7.88), breast pain (OR = 9.36, 95% CI 3.91 to 22.38) and breast discomfort (OR = 6.42, 95% CI 3.62 to 11.37), respectively, at 12 postoperative months. Increasing chest circumference was associated with having ongoing incision pain (OR = 1.12, 95% CI 1.03 to 1.21) and breast pain (OR = 1.10, 95% CI 1.00 to 1.22). Harvesting of bilateral internal mammary arteries (IMAs) was associated with having ongoing incision pain (OR = 4.71, 95% CI 1.54 to 14.3), while harvesting only the left IMA was associated with having ongoing breast pain (OR = 2.78, 95% CI 1.06 to 7.32) and breast discomfort (OR 1.80, 95% CI 1.02 to 3.19). Conclusions: Patients reported incision and breast pain and discomfort as long as 12 months post-sternotomy. Improved management of postoperative pain and discomfort up to at least 12 weeks following surgery may render reduced long-term pain and discomfort symptoms.